Beyond binaries: complex roles and identities in critical mental health research. Issue 4 (22nd April 2022) - Tseris, Emma; Franks, Scarlett; Bright Hart, Eva
Abstract: In this article, we discuss our experiences on a project that is exploring gendered harms experienced by women during involuntary mental health treatment. We outline our journey towards a more complex understanding of our roles in the project, by considering the aspects of our identities that are hidden when situating ourselves only in terms of survivor or non-survivor researchers. In addition, we discuss expectations that are often present in research projects for survivor researchers to publicly disclose highly personal experiences, while non-survivor researchers face no such demands, and the myth of a homogenous survivor researcher identity. We discuss how critiquing binary identities, while still acknowledging power and difference, may open up new ideas about creative and strategic approaches to challenging and resisting psy-oppression.